Gender Dynamics in Social Work Practice and Education: A Critical Literature Review. Issue 1 (2nd January 2019) - Jones, Miriam; Mlcek, Susan H. E.; Healy, John Paul; Bridges, Donna
ABSTRACT: This paper offers a critical analysis of existing literature on historical and contemporary gender dynamics in Australian social work education and practice. Analyses of gender dynamics and inequalities have the potential to illuminate pathways for inclusive social work education and practice, for both practitioners and people who access social work services. This critical review of the literature demonstrates that Australian social work education and practice have been shaped by gendered discourses, structures, and power dynamics since its inception. In a contemporary sense, women constitute the majority of social work educators and practitioners, while men disproportionately dominate positions of power and prestige, although rigorous Australian data on the roles and representation of men and women are not readily available. Our findings point to the need for further engagement with gender as a unit of analysis in Australian social work research, including further engagement with inclusive and intersectional feminisms. IMPLICATIONS Enhanced knowledge of Australian social work history, particularly in relation to gender, allows for a greater understanding of current gendered power relations in social work education and practice. Gender dynamics are underresearched in contemporary Australian social work education and practice. Up-to-date data on the status and representation of men, women, and nonbinary people in social work are needed as the foundation for transformative and inclusive social work education and practice.